The life of Samuel Taylor Coleridge : a critical biography (Blackwell Publishers, 1996)
Presents Samuel Taylor Coleridge - poet, critic, thinker, plagiarist, cultural omnivore, enchanting companion, feckless husband, fabled conversationalist, guilt-ridden opium addict - in his complexity. This biography shows how Coleridge's writings in verse and prose are especially directly expressive of his opinions and emotions.